Multiple mechanisms of hERG liability: K+ current inhibition, disruption of protein trafficking, and apoptosis induced by amoxapine - Metcalfe, Sabrina; Staudacher, Ingo; Ficker, Eckhard; Dennis, Adrienne; Koschny, Ronald; Erdal, Hande; Bloehs, Ramona; Kisselbach, Jana; Karle, Christoph; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (Naunyn-Schmiedeberg's archives of pharmacology, 2010)
The antidepressant amoxapine has been linked to cases of QT prolongation, acute heart failure, and sudden death. Inhibition of cardiac hERG (Kv11.1) potassium channels causes prolonged repolarization and is implicated in apoptosis. Apoptosis in association with amoxapine has not yet been reported. This study was designed to investigate amoxapine effects on hERG currents, hERG protein trafficking, and hERG-associated apoptosis in order to elucidate molecular mechanisms underlying cardiac side effects of the drug. hERG channels were expressed in Xenopus laevis oocytes and HEK 293 cells, and potassium currents were recorded using patch clamp and two-electrode voltage clamp electrophysiology. Protein trafficking was evaluated in HEK 293 cells by Western blot analysis, and cell viability was assessed in HEK cells by immunocytochemistry and colorimetric MTT assay. Amoxapine caused acute hERG blockade in oocytes (IC50 = 21.6 µM) and in HEK 293 cells (IC50 = 5.1 µM). Mutation of residues Y652 and F656 attenuated hERG blockade, suggesting drug binding to a receptor inside the channel pore. Channels were mainly blocked in open and inactivated states, and voltage dependence was observed with reduced inhibition at positive potentials. Amoxapine block was reverse frequency-dependent and caused accelerated and leftward-shifted inactivation. Furthermore, amoxapine application resulted in chronic reduction of hERG trafficking into the cell surface membrane (IC50 = 15.3 µM). Finally, the antidepressant drug triggered apoptosis in cells expressing hERG channels. We provide evidence for triple mechanisms of hERG liability associated with amoxapine: (1) direct hERG current inhibition, (2) disruption of hERG protein trafficking, and (3) induction of apoptosis. Further experiments are required to validate a specific pro-apoptotic effect mediated through blockade of hERG channels.
Im Text ist "+" hochgestellt
Gesehen am 26.05.2023